Enhanced Power and Rechargeability of a Li−O2 Battery Based on a Hierarchical‐Fibril CNT Electrode. (19th December 2012) - Lim, Hee‐Dae; Park, Kyu‐Young; Song, Hyelynn; Jang, Eui Yun; Gwon, Hyeokjo; Kim, Jinsoo; Kim, Yong Hyup; Lima, Márcio D.; Robles, Raquel Ovalle; Lepró, Xavier; Baughman, Ray H.; Kang, Kisuk
<x xml:space="preserve">Abstract</x> Hierarchical carbon electrodes with highly aligned carbon nanotube (CNT) fibrils are fabricated, and it is demonstrated that these electrodes, with aligned pores, can significantly enhance the cyclability and rate capability of Li−O2 batteries. The highly aligned pore structure enables good accessibility of oxygen to the inner electrode, which leads to a uniform deposition of discharge products on the individual CNTs. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>